Peran Guru PAI Dalam Menanamkan Kebiasaan Mengucapkan Kalimat Tayyibah untuk Membentuk Karakter Religius Peserta Didik di SDIT An-Nahl Tabalong - Rusiana; Zahratun Nisa; Esti Qomah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to describe the role of Islamic Religious Education (PAI) teachers in instilling the habit of reciting kalimat thayyibah to develop students' religious character at SDIT An-Nahl Tabalong. This research employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation and analyzed through data reduction, data display, and conclusion drawing. The findings revealed that PAI teachers play significant roles as role models, mentors, motivators, and supervisors in cultivating students' habit of reciting kalimat thayyibah in their daily activities. The habituation practices include reciting basmalah before starting activities, saying hamdalah after completing activities, reciting istighfar and shalawat after congregational prayers, and performing dhikr after Dhuha and Dhuhr prayers. PAI teachers not only teach thayyibah as part of Islamic learning materials but also integrate them into character education through exemplary behavior, continuous habituation, and educational sanctions for students who use inappropriate language. The habituation of kalimat thayyibah contributes positively to the development of students' religious character, as reflected in their gratitude, awareness of worship and polite speech. However, several challenges remain, including the influence of the external environment and students' emotional control, which occasionally leads to the use of inappropriate expressions. Therefore, the successful development of religious character through the habituation of kalimat thayyibah requires continuous guidance and strong collaboration between teachers, schools, and parents.